An evaluation of the course of facial sunscreen coverage and sustainability over an 8-hour workday among outdoor workers - Waritch Kobwanthanakun (2022)
Background: Reapplication of sunscreen every 2 hours is recommended, especially after swimming, sweating, or working outdoors. However, the sustainability of sunscreen during the workday among outdoor workers is still unclear. Objective: To evaluate the course of facial sunscreen coverage and sustainability over an 8-hour workday among outdoor workers. Materials and Methods: This open-label trial included 20 healthy subjects who spend at least 80% of their workday outdoors. All volunteers applied 2 mg/cm2 of provided broad-spectrum sunscreen mixed with the invisible blue fluorescent agent to all parts of their face in the morning. A VISIA-CR camera was used to capture facial fluorescence intensity every 2 hours, and digital image analysis software was used to quantify fluorescence intensity at six areas of the face at each time point for 8 hours. Results: Sunscreen coverage declined most rapidly during the first 2 hours with a mean reduction of 18.31%. By the end of the 8-hour study workday, the mean decrease in sunscreen coverage was 31.63% (range: 17.39%-45.29%). Conclusion: Reapplication of sunscreen is essential among outdoor workers. After 4 hours, the amount of sunscreen remaining on the face may not be sufficient for protecting the skin from harmful ultraviolet radiation.